Illustrated war news, 1914-1918 & 1939. - Illustrated London News (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2023)
Originally released during the First World War, The Illustrated War News was an offshoot of The Illustrated London News (ILN), and it remained under the ownership of the ILN. Though initially published weekly between 1914 and 1918, this periodical was re-launched shortly before the outbreak of the Second World War, and continued publication throughout 1939. Staunchly patriotic, its coverage related exclusively to military matters, focusing on Britain's armed forces and national defence, which the paper portrayed with a combination of full-page photographs and illustrations. This collection incorporates nearly 8,600 images from The Illustrated War News, published between 1914 and 1918, and then January and December 1939. Whilst it constitutes the smallest collection in British Illustrated Periodicals, 1869-1970, the material is particularly important, given its relevance to one of the most significant events of the twentieth century.
Date range: 1914-1918 & 1939.
Keywords: World War, 1914-1918 -- Great Britain -- Periodicals; World War, 1939-1945 -- Great Britain -- Periodicals; Great Britain -- Armed Forces -- Periodicals; Illustrated war news